Response Evaluation of Choroidal Melanoma After Brachytherapy Using Diffusion-Weighted Magnetic Resonance Imaging (DW-MRI): Preliminary Findings - Bitencourt, Flávia B. C. S. N.; Bitencourt, Almir G. V.; Chojniak, Martha M. M.; Souza, Juliana O.; Castro, Douglas G.; Pellizzon, Antônio Cassio A.; Chojniak, Rubens (Frontiers in Oncology, 2020)
Purpose: To evaluate the role of diffusion-weighted magnetic resonance imaging (DW-MRI) in the assessment of therapeutic response in patients with choroidal melanoma treated with brachytherapy. Materials and Methods: We performed a prospective, unicentric study which included patients with choroidal melanoma and indication for brachytherapy. Three DW-MRI examinations were proposed for each patient, one before and two after treatment. The apparent diffusion coefficient (ADC) value was calculated on DW-MRI and compared with local tumor control assessed by ophthalmologic follow-up. Results: From 07/2018 to 06/2019, 19 patients were recruited, 13 of whom underwent follow-up examinations. Patients’ ages ranged from 24 to 78 years and 52.9% were male. At the ocular ultrasound, the mean tumor thickness and diameter were 6.3 mm and 11.5 mm, respectively. Two patients (15.4%) showed signs of tumor progression during follow-up (7 and 9 months after treatment). There was no statistically significant difference in tumor size between MR before and after treatment, however, there was a significant reduction in mean ADC in patients with progression (p = 0.02). Conclusion: DW-MRI has proven to be a useful method for monitoring patients with choroidal melanoma; reduction in the mean ADC values between pre-treatment MRI and the first post-treatment MRI may be related to the lack of response to brachytherapy and increased risk of disease progression.